Colors and their meaning in culture and psychology – a historical outline and contemporary status of color vision theories - Grzybowski, Andrzej; Lewicka, Romana; Torlińska, Teresa; Stelcer, Bogusław (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The mechanism of color perception has intrigued scholars from antiquity. However, the understanding of this phenomena only came with the recognition of the nature of light and visual perception. Ancient concepts, present in science until the Renaissance, were based more on philosophical considerations and theoretical speculations than on anatomical studies and a matter-of-fact assessment of physiological functions of the visual system. From antiquity to 17th century scientific approach to the concept of vision was dominated by two theories: intromission and extramission (emanation). Intromission theory, propagated by Alhazen (Ibn al.-Haythama), Vitello, John Peckham, Roger Bacon and Leonardo da Vinci, assumed that the light was transmitted from the observed object perpendicularly to the transparent eye structures. Johannes Kepler was the first scholar to propose that the retina was the receptive part of the eye. In the first half of the 17th century, Kepler’s groundbreaking optical achievements and anatomical discoveries of many other scientists cast new light on the understanding of the role of different eye structures, finally wiping out the intromission theory. A further major achievement contributing to the recognition of the true nature of colors was a theory presented by Newton in 1688. He argued that they were colored rays, and not white light, that were composed of homogenous and pure light. It was, however, not until the 19th century when two modern theories of color appeared, i.e. a trichromatic theory mostly associated with the names of Young and Hemlholtz, and an opponent colors theory of Hering. In the 20th century, the two theories – previously assumed as contradictory – were joined into the zone theories of color vision. Colors have their cultural and social meanings, as far as a very individual and personal interpretation. In the former function they are used to illustrate some cultural and sociological phenomena; in the latter, they are helpful in psychological analyses of patients. The paper outlines major historical concepts of color perception and the present usefulness of color vision tests in psychology.